Turizem v izbranih slovenskih alpskih turističnih krajih med letoma 1985 in 2003 - Vrtačnik Garbas, Katja (Geografski vestnik, 2005)
In the introduction there is shown the development of tourism in the Alps, where special emphasis is put on the difference between the development of the alpine tourism in Slovenia and the other countries of the alpine arc. The central part of the article presents the survey of tourism in some tourist resorts in the Slovene alpine area in the period 1985-2003, which is marked by the stagnation of tourist trade. Here the authoress compares the tendencies in the development of tourism in individual tourist resorts within Slovenia and at the same time exposes specific features which distinguish the alpine tourism in Slovenia from the other alpine countries in which tourism has developed into a much more intensive economic branch.
Keywords: turistična geografija; turizem; tourism; Slovenia; Slovenija; Alpe; Alps